Improvement of native grassland by legumes introduction and tillage techniques - Syamsu Bahar; S Hardjosoewignjo; I Kismono; O Haridjaja (Indonesian Center for Animal Research and Development (ICARD), 1999)
Improvement of native grassland by legumes introduction and tillage techniques Improvement of native grassland by legumes introduction and tillage techniques A factorial design using three species of legumes (Siratro, Centro and Stylo) and three different of tillage techniques (no-tillage, minimum tillage and total tillage) was applied in this experiment. The results showed that there was no interaction between species and tillage techniques. There was significant reductions on bulk density from 1.23±0.03 g/cm3 (no-tillage) to 1.07±0.02 g/cm3 (minimum tillage) and 1.05±0.03 g/cm3 (total tillage). Also reductions on penetration resistance from 17.47±3.84 kg/cm2 (no-tillage) to 3.31±0.43 kg/cm2 (minimum tillage) and 3.19±0.45 kg/cm2 (total tillage). Otherwise significant increasing on aeration porosity from 12.80±0.80% vol. (no-tillage) to 21.70±0.95% vol. (minimum tillage) and 20.70±0.35% vol. (total tillage). Total tillage gives increased dry matter yield. Also both total tillage and minimum tillage give yields with a higher percentage of legumes compared with no-tillage. It was concluded that total tillage and minimum tillage could be used for improving native grassland. Key words : Improvement, native grassland, legumes, tillage techniques